(untitled) (KULT_online, 2010)
Philipp Horst’s study examines the change in the use of language in the visual arts of the 20th and 21st century. The author observes three stages of this development which roughly correspond to the historical movements of modernism and conceptual art as well as contemporary computer art. Whereas modernist artists may be inspired by poetry (or poets by paintings), their works clearly favour the use of one medium, either the visual or the verbal. In the 1960s, however, conceptual artists attempt to merge visual and verbal elements in order to create an equal balance of the two media in their work. This development eventually leads to a third stage at the beginning of the 21st century, when computer artists create works which can neither be classified as visual nor verbal because these media are fused in order to invent a virtual quality which defies conventional descriptions of art.